Student’s parcel tracking and management system / Farah Izziati Roshidan - Roshidan, Farah Izziati (2020)
Student’s Parcel Tracking and Management System is a system developed to manage student’s parcel tracking and management at Kerawang’s College. Problems in having an issue on determining the parcel recipient during key-in the information process because the student do not provide the exact details of themselves on the parcel. Besides, the redundancy of student’s name in the list because of manually process and staff notify the student regarding their' parcel through a piece of paper on Kerawang’s College notice board. Thus, Student’s Parcel Tracking and Management System is proposed to manage the parcel management between staff and student. The system capable for the staff and student to add the information about the parcel and for the student, they can add the remark regarding their parcel. Via this system, the student will receive the notification regarding their parcel if arrived. The notification deliver is through the system and SMS. Student’s Parcel Tracking and Management System was developed by following Adapted Waterfall Model of SDLC. The methodology consists of five phases which are planning process, analysis process, design process, development process, and testing and evaluation process. Functionality testing had been conducted for the user based on the scenario and test cases in order to test on the functionality of the system as well as user evaluation to gauge the feedback on the usability of the system by using usability metrics approach. The overall result of the user evaluation shows that Student’s Parcel Tracking and Management System is user friendly interface and easy to use.